2007
DOI: 10.1016/j.pain.2007.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between alexithymia and hypersensitivity to visceral stimulation in human

Abstract: Empirical studies indicate that alexithymia exacerbates physical illness. However, direct evidence to explain the mechanism of this exacerbation has not been provided. One hypothesis is that alexithymics amplify unpleasant internal signals. In the present study, we investigated how alexithymia influences sensitivity to visceral stimulation in human. In 45 non-clinical healthy subjects (34 males and 11 females), brain processing of visceral sensation induced by colonic distension was examined using H(2)(15)O po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
95
4
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 55 publications
10
95
4
2
Order By: Relevance
“…Studies on healthy volunteers have shown a positive relationship between alexithymia and measures of pain sensitivity during experimental pain induction (26,27). A similar association has been described in general medical patients, and whether a relationship between alexithymia and experimental pain sensitivity exists in patients with chronic pain remains unclear (28).…”
Section: Introductionmentioning
confidence: 89%
“…Studies on healthy volunteers have shown a positive relationship between alexithymia and measures of pain sensitivity during experimental pain induction (26,27). A similar association has been described in general medical patients, and whether a relationship between alexithymia and experimental pain sensitivity exists in patients with chronic pain remains unclear (28).…”
Section: Introductionmentioning
confidence: 89%
“…On the one hand, individuals with elevated alexithymia can exhibit hypersensitivity to sensory input, such as lower tolerance of pain and heat, and over responsiveness to visceral stimulation (Kano et al 2007;Katz et al 2009;Nyklicek and Vingerhoets 2000). On the other hand, they also show reduced awareness and registration of internal bodily signals (Ernst et al 2014).…”
Section: Alexithymia and Sensory Processing Atypicalitiesmentioning
confidence: 99%
“…Bird and Cook (2013) have suggested that emotion recognition and empathy atypicalities seen in individuals with ASD may result from (co-occurring) alexithymia rather than ASD itself. Furthermore, given that alexithymia is associated with higher rates of anxiety and depression (Bankier et al 2001;Berthoz et al 1999;Honkalampi et al 2000) and atypical responses to sensory input (Herbert et al 2011;Kano et al 2007;Katz et al 2009;Lyvers et al 2014;Nyklicek and Vingerhoets 2000) in non-ASD populations, individual differences in alexithymia may also be associated with the increased rates of internalising disorders and sensory sensitivities in ASD. Taylor et al (1999) propose that alexithymia is primarily a disorder of affect regulation, leading to difficulties in modulating the autonomic nervous system, thus resulting in hyper-arousal in response to stress.…”
mentioning
confidence: 99%
“…48 Les sujets alexithymiques présentent une augmentation des marqueurs circulants de l'inflammation (Honkalampi, 2011), une réduction plus lente de l'activation neurovégétative à la suite d'un stress (Halpern, 2012) et une hypersensibilité aux stimuli désagréables d'origine externe (Schäfer, 2007) ou interne (Kano, 2007), objectivée par le constat d'une activation plus importante des zones concernées du cortex cérébral.…”
Section: Fréquence Et Populations Concernéesunclassified